2015
DOI: 10.1111/asj.12516
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term impact of puerperal metritis on the profiles of peripheral blood leukocytes in peripartum dairy cows

Abstract: To determine the effects of puerperal metritis on the immune response, changes in the differential peripheral blood leukocyte counts were analyzed during the peripartum period in cows with or without metritis. Multiparous Holstein cows were examined for uterine health disorders and classified into two groups: healthy (n = 11) or metritis (n = 5) cows. The lymphocyte and monocyte counts and the proportion of CD8(+) lymphocytes were higher in cows with metritis compared to healthy cows. Moreover, the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Previous work has demonstrated an increase in the number of total lymphocytes during the periparturient period in cows with metritis, specifically two weeks prior to calving (Magata et al, 2016). Interestingly, these studies also demonstrated an increase in the number of CD8 + lymphocytes in the week preceding calving in opposition to our own data here, which suggests there is no difference in the proportion of prepartum CD3 + /CD8 + in cows that go on to develop uterine disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated an increase in the number of total lymphocytes during the periparturient period in cows with metritis, specifically two weeks prior to calving (Magata et al, 2016). Interestingly, these studies also demonstrated an increase in the number of CD8 + lymphocytes in the week preceding calving in opposition to our own data here, which suggests there is no difference in the proportion of prepartum CD3 + /CD8 + in cows that go on to develop uterine disease.…”
Section: Discussionmentioning
confidence: 99%
“…Uterine disorders, such as endometritis, are commonly observed in high-producing dairy cows and often cause poor reproductive performance, reduced milk yield, and consequently, result in economic loss ( 1 3 ). The endometrium is a natural barrier, and endometrial epithelial cells can resist the invasion of foreign pathogens by regulating the immune inflammatory response ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Uterine diseases are prevalent in dairy cows, cause poor reproductive performance, reduced milk yield, and substantial economic losses 1 2 3 . Uterine diseases can be classified as puerperal metritis, clinical metritis, clinical endometritis and subclinical endometritis 4 5 6 .…”
mentioning
confidence: 99%